Further Education and Training Act nº16, 2006 - Government of South Africa (2006)
Also known as Continuing Education and Training Act.
UA-12d0a561-668e-4da9-9506-2693c36aeb96 KerkoCite.ItemAlsoKnownAs: 2129771:3HJSUHG7 2317526:H2K8DC4E
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:South Africa; publicImportV1